A practical fully automated radiosynthesis of [18F]Flurpiridaz on the module modular lab-pharmtracer without external purification - Kurtulus Eryilmaz; Benan Kilbas (SpringerOpen, 2022)
Abstract Background [18F]Flurpiridaz is a promising novel cardiac PET imaging tracer formed by the radiolabeling of pyridaben derivative with fluorine-18. Clinical studies on [18F]Flurpiridaz are currently at the phase III level for the assessment of MPI. Providing high image quality thanks to its relatively long half-life, F-18 is a high-potential radionuclide for the early detection of CAD. In this study, we aimed to develop a fully automated synthesis of [18F]Flurpiridaz without further preparative HPLC purification. Results Precursor 6 was obtained by multi-step synthesis starting from mucochloric acid (1) as a sole product with 35% yield and identified by spectroscopic measurement. Manually cold labeling experiments were performed using the stable isotope [19F]F, and TBA-HCO3 PTC provided desirable fluorinated compound with high yield. A fully automated [18F]Flurpiridaz synthesis on the ML-PT device provided 55-65% radiochemical yield with more than 98% radiochemical purity. The final product purification method demonstrated that [18F]Flurpiridaz could be obtained without an external preparative HPLC system as a pharmaceutical quality. Conclusion A novel and fascinating strategy was developed for the fully automated synthesis of [18F]Flurpiridaz (7) on ML PT. Organic synthesis of precursor 6 was achieved with a desirable yield and characterized by NMR and HR-MS. A detailed set of cold experiments were completed for optimization conditions before hot trials and TBA-HCO3 increased molar activity with a minimum amount of side products. Radiolabeling showed that our self-designed automated synthesis method enables high radiochemical yield and radiochemical purity for the production of [18F]Flurpiridaz. The desirable radiopharmaceutical quality of the product was obtained without using an additional preparative HPLC system. [18F]Flurpiridaz (7) preserved its stability within 12 h and final specifications were consistent with the acceptance criteria in Ph. Eur. regulations.